2020
DOI: 10.1016/j.jdiacomp.2019.107518
|View full text |Cite
|
Sign up to set email alerts
|

Newly diagnosed abnormal glucose tolerance determines post-MI prognosis in patients with hospital related hyperglycaemia but without known diabetes

Abstract: In patients without known diabetes, abnormal Q3 glucose tolerance (AGT), diagnosed on the 2 hour post load plasma glucose (2h-PG) and not admission plasma glucose (APG), determines post-MI prognosis.• AGT, mainly newly diagnosed DM, determines prognosis in patients with and without hospital related hyperglycemia (HRH).• AGT imposes an additional post-MI prognostic risk in patients without HRH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The database searching process yielded a total of 2157 articles with 761 duplicates so a total of 1396 articles entered the title and abstract screening. A total of 1369 articles were excluded and then 27 articles were screened by full-text to yield a total of 19 articles (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) for the meta-analysis. (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The database searching process yielded a total of 2157 articles with 761 duplicates so a total of 1396 articles entered the title and abstract screening. A total of 1369 articles were excluded and then 27 articles were screened by full-text to yield a total of 19 articles (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) for the meta-analysis. (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In patients without diabetes, admission blood glucose alone without HbA1c values to test for undiagnosed diabetes or prediabetes and without post-discharge tests to assess the glycaemic state after the drop of stress during hospital admission, the meaning and interpretation of admission hyperglycaemia in clinical practice is difficult. [46][47][48][49] We cannot exclude the possibility that the outcome in the group without diabetes was driven by pre-diabetes or undiagnosed diabetes. Furthermore, there is a lack of information on the effect of in-hospital treatment regarding hyperglycaemia and hypoglycaemia, and how glucose levels during hospital stay affected adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…and 22% higher risk of CVD and CHD, respectively. Moreover, finding of some studies showed that IGT was associated with worse post MI prognosis [9,22] while some showed no significant risk [26] and study by George et al [23] revealed that IGT is associated with higher risk of MACE but not hard CVD outcomes. The findings of our study however, showed that the risk of CVD/CHD and the related hard outcomes does not increase among those with IGT; in line with other studies conducted among low risk population with prevalent CAD [8,34].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the newly diagnosed diabetes using 2 h-PCPG criteria, most studies showed that newly diagnosed diabetes [21,26] or AGT (newly diagnosed diabetes using 2 h-PCPG definition plus IGT) are independently associated with higher risk of different cardiovascular outcomes [9][10][11][24][25][26]. In the current study however, when using 2 h-PCPG criteria, a moderate higher risk of hard CHD 2.02 [(0.91-4.47), P = 0.08] was seen among those with newly diagnosed diabetes.…”
Section: Discussionmentioning
confidence: 99%